Resurgence of Mumps among Lower Socioeconomic Class of Children in Ahmedabad: A Cross-sectional Study of 115 Cases in a Tertiary Care Center - Dipti V Patel; Zeel Patel; Snehal V Patel; Pooja Gandhi; Gayatri Parmar; Param S Patel (Pediatric Infectious Disease)
Aims and background: Mumps has seen a resurgence in the lower socioeconomic regions of Ahmedabad. The present study was undertaken to study the clinical pattern among mumps patients and their vaccination status. Materials and methods: A hospital-based cross-sectional study was carried out in the Department of Pediatrics at Shardaben General Hospital (NHL Municipal Medical College), a tertiary care center located in Saraspur, Ahmedabad, from September to December 2023. All patients 12 years of age who were clinically diagnosed with mumps on an outpatient department (OPD) basis and those admitted to the pediatric ward with mumps and its complications were included in the study. All patients belonged to the lower socioeconomic class of Ahmedabad. Informed consent was obtained from patients' relatives. Detailed history in the form of demographic data, clinical presentation, vaccination status for measles–rubella (MR)/measles–mumps–rubella (MMR), reasons for nonvaccination, and history related to complications. A detailed physical examination was performed, and the data was tabulated in an Excel sheet. An appropriate statistical analysis using percentage calculation was performed. Results: It was observed that out of a total of 115 patients who were clinically diagnosed with mumps, the highest occurrence (71.3%) was observed among the 6–10 years age-group. No patient was fully vaccinated for mumps. Out of the 15.6% (18 patients) admitted, two patients (1.7%) suffered from mumps complication of orchitis. Around 24.3% of mumps patients had no contact history, whereas the rest, 75.6%, had either a classroom or household contact history with a mumps patient. Mumps also resulted in increased hospital burden and school absenteeism. Conclusion: It is high time that the Indian Academy of Pediatrics and the Government of India join hands to include MMR in place of MR in the National Immunization Schedule (NIS) and conduct a mass campaign for the MMR vaccine, although three doses of MMR in the 2023 Indian Academy of Pediatrics (IAP) Advisory Committee on Vaccines and Immunization Practices (ACVIP) recommendation. Clinical significance: Mumps is a public health problem in India. Though a benign disease, it has the potential for multiple complications. Effective vaccines are available to prevent the disease. So why not protect our future generations from it?